BepiColombo’s Cruise Phase: Unique Opportunity for Synergistic Observations - Hadid, L. Z.; Génot, V.; Aizawa, S.; Milillo, A.; Zender, J.; Murakami, G.; Benkhoff, J.; Zouganelis, I.; Alberti, T.; André, N.; Bebesi, Z.; Califano, F.; et al. (Frontiers in Astronomy and Space Sciences, 2021)
The investigation of multi-spacecraft coordinated observations during the cruise phase of BepiColombo (ESA/JAXA) are reported, with a particular emphasis on the recently launched missions, Solar Orbiter (ESA/NASA) and Parker Solar Probe (NASA). Despite some payload constraints, many instruments onboard BepiColombo are operating during its cruise phase simultaneously covering a wide range of heliocentric distances [0.28 AU - 0.5 AU]. Hence, the various spacecraft configurations and the combined in-situ and remote sensing measurements from the different spacecraft, offer unique opportunities for BepiColombo to be part of these unprecedented multipoint synergistic observations and for potential scientific studies in the inner heliosphere, even before its orbit insertion around Mercury in December 2025. The main goal of this report is to present the coordinated observation opportunities during the cruise phase of BepiColombo (excluding the planetary flybys). We summarize the identified science topics, the operational instruments, the method we have used to identify the windows of opportunity and discuss the planning of joint observations in the future.